The Influence of Tax Understanding, Reduction of Final PPH Tax Rates, and Tax Sanctions on the Compliance of Micro, Small, and Medium Enterprises (MSMEs) Taxpayers (Case Study on Batik MSMEs in Jambi City) - Arya Satria; Wiwik Tiswiyanti; Salman Jumaili (International Journal of Scientific Multidisciplinary Research, 2024)
This research aims to determine the effect of understanding taxation, reducing the final PPH tax rate and tax sanctions on taxpayer compliance. This research was conducted on batik MSME in Jambi City. The number of samples used in this research was 104 (one hundred and four) MSME actors with the sampling method being a saturated sample. The data analysis technique used in this research is SPSS 27. The results of this research show that understanding taxation is positive and significant on taxpayer compliance, reducing the final PPH tax rate has a positive and significant effect on taxpayer compliance. Meanwhile, tax sanctions have a negative and insignificant effect on taxpayer compliance